Sexual selection and genital allometry in the Hottentot golden mole (Amblysomus hottentotus) - Retief, T.; Bennett, N.; Kinahan, A.; Bateman, Bill (Urban und Fischer Verlag, 2013)
Under sexual selection, genitalia typically undergo rapid and divergent evolution across species and competitionbetween the sexes over control of fertilisation may drive the co-evolution of male and femalesexual traits. Sexual selection can, therefore, influence genitalia in three fundamental but non-mutuallyexclusive ways: (1) cryptic female choice, (2) sperm competition and (3) sexual conflict. Golden moles(Chrysochloridae) are a highly specialised family endemic to sub-Saharan Africa. We examined intraspecificgenital allometry of both male and female subterranean Hottentot golden moles (Amblysomushottentotus). Consistent with previous studies in mammals, we found positive allometry and a high coefficientof variation (CV) for male genitalia. The results for female reproductive tract length of A. hottentotuscontrast with the findings of previous studies as isometry was recorded. Based on the allometric relationshipsof both males and females presented here, we suggest that the males do not sequester femalesand that in the absence of visual cues the female may use penis size as an indicator of phenotypic quality.